An Empirical Study of Tax as an Instrument of Democratization - Irianto, Edi Slamet (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2013)
This article proposes two focuses on the discussion on fiscal decentralization carried out by the government and the important role that taxation in bringing about the process of economic democratization. Taxation is one of the most crucial factors in the strengthening of the role of the government especially the role of tax in budgetary issues. The two issues are strategic for a mutual relationship between the state and its citizen, the state in its legal authority to collect tax from its citizens and on the other hand the citizens to pay taxes as part of its submission to the existing law.